Sustitución y obra nueva “Escuela Inem Manuel Murillo Toro sede Pablo Sexto” - Bonilla Vega, Anggie Milena (Universidad Antonio Nariño, 2022)
This project will be developed in the municipality of Ibagué in commune 2 in the neighborhood Ancon. In this sector there are social and environmental problems that affect the community development and quality of life. In commune 2 it has been identified that 93% of the population knows how to read and write, while that 7% do not, 28% only studied primary school, 43% attend secondary school, 10% have a technician, 2% technologist and 11% professional level. It was also found that the level of schooling in children reaches 6%, a worrying figure considering that 30% of the population of the commune is within the age range of childhood